1999
DOI: 10.2114/jpa.18.91
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Biomechanical Characteristics on Body Segments of Koreans.

Abstract: This paper documents the physical measurements of the Korean population in order to construct a data base for ergonomic design. The dimension, volume, density, mass, and center of mass of Koreans whose ages range from 7 to 49 were investigated. Sixtyfive male subjects and sixty-nine female subjects participated. Eight body segments (head with neck, trunk, thigh, shank, foot, upper arm, forearm and hand) were directly measured with a Martin-type anthropometer, and the immersion method was adopted to measure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Head volume measured by the immersion method (m V H ) was based on Archimedes' principle (Park, Kim, & Park, 1999). Each participant slowly inserted his or her head into a container filled with water, which could hold the whole head, up to a horizontal reference mark.…”
Section: Methodsmentioning
confidence: 99%
“…Head volume measured by the immersion method (m V H ) was based on Archimedes' principle (Park, Kim, & Park, 1999). Each participant slowly inserted his or her head into a container filled with water, which could hold the whole head, up to a horizontal reference mark.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the average weight of geriatric rehabilitation patients in France has been estimated at 60kg [40], more recently in Egypt a cohort of geriatric patients averaged 76kg [41] whilst US data puts the average weight of someone in the general population who is 70+ years old as 72kg [42]. Our selected weight of 300kg in the rig set up is therefore compatible with a typical hospital bed weighing 191kg [43] and an adult 70+ years old in the 95th percentile for weight [42].…”
Section: Assessmentmentioning
confidence: 99%
“…These data, like the previous, refer to Caucasian men. Only relatively recently inertial parameters have been published, in relation to different genders and races [18,19], and norms for Asian men were also provided [20][21][22]. There have been attempts to profile a single state population or special small populations, for example, a study on Bulgarian [23] or Indonesian population which showed very different distributions in dimensions, COM location and inertial parameters of these populations in comparison to Caucasian [24].…”
Section: Modern and Contemporary Timesmentioning
confidence: 99%